Facilitators of Adolescent Girls' Access to Sexual and Reproductive Health Services in Iran: A Qualitative Study - Seyed Abbas Mosavi; Khadijeh Mirzaii; Mohammad Shariati; Raheleh Babazadeh (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Investment in the adolescents' health is an effective way to improve the public health. Objectives: This study aimed to explore the views and experiences of adolescent girls and key adults to identify the facilitators of access to sexual and reproductive health services among Iranian adolescent girls. Methods: In this qualitative study, the data were gathered through focus groups and semi-structured interviews with 247 adolescent girls and 71 key adults in Iran. The collected data were coded and categorized using a content analysis method in MAXQDA v10. Results: The main facilitators of Iranian adolescent girls' access to reproductive health services were classified into five categories: 1) Factors associated with policymaking, such as governmental support; 2) benefiting from the religion's potentials; 3) social and cultural factors, such as creating a supportive environment in the community; 4) public participation; and 5) factors associated with the methods of service delivery. Conclusion: The governments' acceptance of sexual health education shortcomings is the most important factor affecting the successful implementation of reproductive health programs for Iranian adolescents. Overall, increasing public participation and intersectional collaboration, besides creating a supportive environment in the community, is the next step in improving sexual health education.